Risk factors for severe adverse drug reactions in hospitalized patients - Petrović Nemanja Z.; Pejčić Ana V.; Milosavljević Miloš N.; Janković Slobodan M. (Open Medicine)
Severe adverse drug reactions (sADRs) are becoming increasingly common nowadays. The incidence of sADRs is approaching 6.7%, and the incidence of fatal adverse reactions is 0.32% in hospitalized patients. Of these, 48.5% are, at least potentially, preventable.